Gambaran Kesiapsiagaan Warga dalam Menghadapi Bencana Tanah Longsor di Dukuh Gesikan Desa Jrakah Selo Boyolali - Putri Wulandari; Irma Mustika Sari (Jurnal Anestesi, 2024)
Landslides are geological disasters that can cause fatalities and large material losses, caused by uneven and unstable soil structures. Objective: To obtain an overview of residents' preparedness in facing landslides in Dukuh Gesikan, Jrakah Selo Boyolali Village. Method: This research uses a descriptive survey method with a sample size of 76 respondents and uses a stratifiet random sampling technique. Results: The results showed that based on the characteristics of the respondents, the majority were in the age range 26-45 years (48.7%), male (56.6%), junior high school education (44.7%). The general results showed that the preparedness of the residents of Dukuh Gesikan, Jrakah Selo Boyolali Village was in the "Almost ready" category. This is shown in the preparedness indicators, it is known that the level of knowledge is very ready (84.2%), emergency response plans are ready (44.7%), policies are almost ready (47.4%), resource mobilization is less ready (51.3% ), less prepared disaster warnings (46.1%). Conclusion: The description of residents' preparedness in facing landslides in Dukuh Gesikan, Jrakah Selo Boyolali Village is in the almost ready category with the preparedness index results obtained at (46.1%).